Upconversion nanoparticles for in vivo applications: limitations and future perspectives. (26th February 2019) - del Rosal, Blanca; Jaque, Daniel
Abstract: UCNPs have attracted a great deal of attention as near infrared-excited luminescent probes for biomedical applications. UCNPs can provide contrast for in vivo imaging, act as luminescent temperature reporters and excite different molecules to trigger therapeutic processes. While the unique features of UCNPs are well-suited for certain applications, their intrinsic limitations may prevent their general use in preclinical and clinical settings as luminescent probes. In this work, we analyze the role of UCNPs in research in small animal models. The evolution in the field, from the early studies evaluating UCNPs for in vivo fluorescence imaging to the most recent applications, is described, and the advantages and limitations of UCNPs for different applications are discussed. Their adequacy for preclinical research and potential clinical application are also discussed.